Design and Implementation of the Digital Twin Software Platform for Complex Rotor System - Cui, Ze-wen; Luo, Zhong; Li, Lei; Sun, Kai; Wu, Dong-ze (Journal of Vibration Testing and System Dynamics, 2026)
Aiming at the problems that the complex rotor system is difficult to carry out and monitor due to variable load and bad working conditions, the design method of software platform based on digital twin technology is studied, and the architecture and main function realization of digital twin software platform are explored from six aspects: physical layer, virtual layer, data layer, functional layer, client layer and connection layer. A method to establish the digital twin model of rotor system integrating geometric model and mechanism model is proposed. The digital twin model of the existing rotor test-bed is constructed. Based on the digital twin software platform of the rotor test-bed, the rationality of the design and implementation method is verified by comparison with the experiment.